-DESIGN OF DEFENCE SCHEME IN POWER SYSTEM USING ADAPTIVE LOAD SHEDDING AND REMEDIAL ACTION SCHEME - Made Dwi Darmantara, I
The electric power system is an interconnected system that includes power generation, transmission, and distribution. Large disturbances in the system such as super contingency can cause system instability problems. Load shedding scheme can be used to restore the stability of the system so as to avoid a blackout. But the conventional load shedding has disadvantages such as failing to restore stability and this scheme sometimes releases a load that is incompatible with the value of disturbance and causes a loss. This has led to the need to develop a more effective load shedding method. The purpose of this study was to develop an adaptive load shedding design using the RAS system, based on a large disturbance in the system. The object of research is the Muara Karang sub-system. The rate of frequency decline in each generator is measured to calculate the value of system disturbance. The voltage sensitivity in each busbar is measured to determine the location and the amount of load shedding in each busbar. This system is simulated using DIgSILENT PowerFactory software with an event-based RAS scheme based on three different types of super contingency in the system. The frequency, rotor angle, and voltage results are displayed to see the system stability response after a disturbance with RAS-based adaptive load shedding mitigation systems.